Impact of vitamin E and selenium supplementation on growth, reproductive performance, and oxidative stress in dexamethasone-stressed Japanese quail cocks - Ifeanyi Emmanuel Uzochukwu; Luke Chukwudi Ali; Bright Chigozie Amaefule; Chisom C. Okeke; Charles Onochie Osita; Ndubuisi Samuel Machebe; Vesela Yancheva; Dóra Somogyi; Krisztián Nyeste (Poultry Science)
This study investigated the effects of dietary vitamin E (VE) and selenium (Se) supplementation on body weight changes, blood profile, and semen quality in Dexamethasone (DEX)-stressed Japanese quails. One hundred and five 10-week-old quail cocks were acclimated and divided into five treatment groups: negative control – G1, DEX-treated (20 mgL−1 of drinking water) – G2, DEX + VE (180 mg kg diet−1) – G3; DEX + Se (0.3 mg kg diet−1) – G4; and DEX + VE (180 mg kg diet−1) + Se (0.3 mg kg diet−1) – G5. The birds received their respective treatments over 21 days, and various performance, hematological, and semen quality parameters were measured. Results indicated that DEX treatment significantly reduced weight gain (WG) and feed intake (P < 0.05). Supplementation with VE and Se, individually and combined, ameliorated these effects, with groups G3, G4, and G5 showing similar WG to the control. Hematological analysis revealed significant increases (P < 0.05) in packed cell volume, hemoglobin, and white blood cell count in DEX-treated groups compared to G1. Treatment did not affect blood glucose and cholesterol levels (P ≥ 0.05). Plasma antioxidant assays showed elevated superoxide dismutase and catalase functions and reduced malondialdehyde levels in G3, G4, and G5 compared to G2, indicating reduced oxidative stress. No marked differences were seen in the plasma glutathione peroxidase activities across groups. Sperm motility was impaired in the DEX-only group but improved (P < 0.05) with antioxidant supplementation. In conclusion, dietary VE and Se effectively mitigated the negative impacts of DEX-induced stress on growth, antioxidant status, and spermatozoa motility in Japanese quail cocks. VE and Se supplementation could be beneficial in enhancing the welfare and productivity of poultry under stress.